Solitary synchronous gastric metastasis of renal cell carcinoma - Koterazawa, Shigeki (IJU Case Rep, 2020)
INTRODUCTION: There have been some reports describing metastasis to the stomach from renal cell carcinomas. However, there are few reports describing solitary synchronous gastric metastasis of renal cell carcinomas. CASE PRESENTATION: The patient was a 70‐year‐old woman who underwent an upper gastrointestinal endoscopy to examine her progressive weight loss. There was a submucosal tumor in the stomach, which was biopsied. The gastric tumor was pathologically proven to be a metastatic clear cell renal cell carcinoma. Furthermore, contrast‐enhanced computed tomography showed right renal cell carcinoma invading the renal vein (cT3aN0M0). The patient underwent right radical nephrectomy and endoscopic resection for the treatment of the primary renal cancer and the gastric metastatic lesion, respectively. The resected specimen of the stomach had a clear resection margin. CONCLUSION: Endoscopic resection for early stage gastric metastatic lesions of renal cell carcinomas is a reasonable approach because it is a minimally invasive surgical technique.